THE EFFECT OF READ, ENCODE, ANNOTATE, PONDER (REAP) STRATEGY AND READING INTEREST ON READING COMPREHENSION ACHIEVEMENT - Suhaimi, Suhaimi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2017)
Applying appropriate teaching strategy can give huge contribution to studentsâ achievement. This study investigated the effects of Read, Encode, Annotate, Ponder (REAP) strategy and reading interest on reading comprehension achievement (RCA) of the third semester students of English study program at IAIN Kerinci by applying experimental research method with factorial design. A questionnaire was distributed to the population to find out their reading interest level. Forty students were divided into Experimental and Control groups equally; they were given reading comprehension test as the pre-test and post-test to measure their RCA. The results indicated that REAP strategy significantly improved studentsâ RCA. Moreover, although the interaction effect between REAP strategy and reading interest on studentsâ RCA was not found, the mean difference of the post-test scores from the whole sample indicated that the achievement of High reading interest students were significantly better than Low reading interest students. These results suggest that English teachers should apply various appropriate teaching strategies and monitor studentsâ reading interest while teaching reading.